PERSEPSI MAHASISWA TERHADAP PELAYANAN ADMINISTRASI PEGAWAI BIRO ADMINISTRASI AKADEMIK DAN KEMAHASISWAAN (BAAK) DI UNIVERSITAS NEGERI PADANG - Randi Lefino Saputra (Universitas Negeri Padang, 2014)
The goal of this research are to see information about UNP student perception of the service employees in the UNP BAAK. The popolation is 31122 UNP student from year 2007 to 2013 and the sample is 100 people that taken by random. Sampling research the instrument of this research is avestion with likert scale models that had tested for validity abd reliability. Data analized using mean score. The results shawed that the administration of employe service BAAK be in other category. Keyword: perception and administration services